2020
DOI: 10.1177/1524839920945927
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Mortality in American Adults: Results From the NHANES-Linked Mortality Study

Abstract: Food insecurity is a significant public health problem in the United States leading to substantial social, economic, and health care–related burdens. While studies continue to estimate the prevalence of food insecurity, the long-term outcomes are not extensively explored. The purpose of this study was to assess the impact of food insecurity on mortality. We analyzed data on adults (≥ 20 years) from the 1999–2010 National Health and Nutrition Examination Survey, with mortality data obtained through 2015. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 38 publications
(93 reference statements)
0
58
0
Order By: Relevance
“…These social determinants of health have long influenced the health of Americans. Policymakers and public health practitioners should redouble their efforts in preventing stress-related morbidity and premature mortality by implementing interventions that address the negative and detrimental social determinants of health [8,10,[14][15][16] The results of this study suffer from all traditional limitations of cross-sectional study designs (e.g., social desirability, self-reported data, and the inability to establish cause and effect). Also, our sample might have limitations due to the online survey deployment option, which required an internet connection and a reasonably higher level of literacy to answer computer surveys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These social determinants of health have long influenced the health of Americans. Policymakers and public health practitioners should redouble their efforts in preventing stress-related morbidity and premature mortality by implementing interventions that address the negative and detrimental social determinants of health [8,10,[14][15][16] The results of this study suffer from all traditional limitations of cross-sectional study designs (e.g., social desirability, self-reported data, and the inability to establish cause and effect). Also, our sample might have limitations due to the online survey deployment option, which required an internet connection and a reasonably higher level of literacy to answer computer surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Given such financial insecurity and emotional challenges, it is not surprising that stress was a contributor to unhealthy dietary patterns in our study population. Solving the problems of unemployment, job insecurity, associated stress, and food insecurity requires robust fiscal policies, social protection, and community-based approaches to reducing deprivation and inequalities [ 14 , 15 , 16 ]. These social determinants of health have long influenced the health of Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations include ongoing and enhanced COVID-19-specific CalFresh benefits. Whether federal and California-specific safetynet benefits will have a lasting effect on levels of VLFS and, in turn, chronic diseases associated with food insecurity (10,11), requires ongoing study.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Banerjee and colleagues [ 51 ] showed that people experiencing FI had a 58% higher risk of mortality compared to those not reporting FI. Mortality risk differed by level of FI, with very low food security (HR=2.00, CI:1.16, 3.44) showing the highest risk followed by marginal food security (HR=1.79, CI: 1.10, 2.93) and low food security (HR=1.21, CI:0.64, 2.29).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Mortality risk differed by level of FI, with very low food security (HR=2.00, CI:1.16, 3.44) showing the highest risk followed by marginal food security (HR=1.79, CI: 1.10, 2.93) and low food security (HR=1.21, CI:0.64, 2.29). When controlling for pre-existing CVD conditions (e.g., myocardial infarction, congestive heart failure), FI had an independent effect on CVD mortality, thereby demonstrating FI’s importance in determining risk profiles for CVD mortality [ 51 ]. While most studies centered on FI and the risk of CVD, Charkhchi and colleagues [ 52 ] used the 2015 Behavioral Risk Factor Surveillance System (BRFSS) to establish a reverse relationship between CVD and increased odds of FI (OR=1.75, 95% CI: 1.12–2.73).…”
Section: Cardiovascular Diseasementioning
confidence: 99%